Public research and the quality of inventions: the role and impact of entrepreneurial universities and regional network embeddedness - Holger Graf; Matthias Menter (Small Business Economics, 2021)
The positive effect of public research on industrial innovations is beyond controversy: public research institutions produce knowledge that is subsequently transferred into product and process innovations by private businesses. Besides this rather passive role in commercializing inventions, public research institutions may also proactively exploit new knowledge through public sector entrepreneurship activities. Especially entrepreneurial universities are perceived as a conduit of knowledge spillovers; they serve as central actors of innovation networks and stimulate network activities. Whereas the linkages between network embeddedness and innovation activities have been largely explored, the determinants of patent quality in terms of radicalness, originality, and generality remain rather unclear. Considering Germany's diverse public research infrastructure (universities, polytechnics, and non-university research institutes), our findings reveal that the type of institution and the corresponding scientific orientation (basic vs applied research) matter for the quality of inventions. The centrality of respective institutions within innovation networks reinforces the radicalness of inventions. However, we do not find support for the general assumption that an entrepreneurial orientation of public sector entities augments the quality of inventions. We conclude the paper with policy recommendations and with future avenues of research. Plain English Summary This study explores the relation between network embeddedness, scientific orientation, entrepreneurial orientation, and the quality of inventions of public research. Our results imply that a basic research focus induces inventions that are more radical, and a more central network position reinforces the production of more radical, original, and general patents. In contrast, an entrepreneurial orientation does not seem to stimulate a higher quality of inventions. Our results give impetus to nuanced public sector entrepreneurship policies that take the type of institution and the optimal level of regional embeddedness into account. A sole focus on the entrepreneurial transformation of public research institutes may not be sufficient to leverage the full potential of knowledge created therein. Instead, more support and guidance for creating links with other network entities is needed along with incentives to commercialize new knowledge.
Keywords: L26; O31; O32; O34; 330; Patent quality; Radical innovation; Entrepreneurial university; Network embeddedness; Centrality